Effect of whitening agents on dentin bonding - Spyrides, George M.; Perdigão, Jorge; Pagani, Clóvis [UNESP]; Araújo, Maria Amélia M. [UNESP]; Spyrides, Silvana M.M. (My University, 2000)
Background: Several studies have shown a reduction in enamel bond strengths when the bonding procedure is carried out immediately after vital bleaching with peroxides. This reduction in bond strengths has become a concern in cosmetic dentistry with the introduction of new in-office and waiting-room bleaching techniques. The aim of this in vitro study was to evaluate the effect of three bleaching regimens: 35% hydrogen peroxide (HP), 35% carbamide peroxide (CP), and 10% CP, on dentin bond strengths. Materials and Methods: One hundred and twenty fresh bovine incisors were used in this study. The labial surface of each tooth was ground flat to expose dentin and was subsequently polished with 600-grit wet silicon carbide paper. The remaining dentin thickness was monitored and kept at an average of 2 mm. The teeth were randomly assigned to four bleaching regimens (n = 30): (A) control, no bleaching treatment; (B) 35% HP for 30 minutes; (C) 35% CP for 30 minutes; and (D) 10% CP for 6 hours. For each group, half of the specimens (n = 15) were bonded with Single Bond/Z100 immediately after the bleaching treatment, whereas the other half was bonded after the specimens were stored for 1 week in artificial saliva at 37°C. The specimens were fractured in shear using an Instron machine. Results: For the groups bonded immediately after bleaching, one-way analysis of variance (ANOVA) followed by the Duncan's post hoc test revealed a statistically significant reduction in bond strengths in a range from 71% to 76%. For the groups bonded at 1 week, one-way ANOVA showed that group B (35% HP for 30 min) resulted in the highest bond strengths, whereas 10% CP resulted in the lowest bond strengths. Student's t-test showed that delayed bonding resulted in a significant increase in bond strengths for groups B (35% HP) and C (35% CP); whereas the group bleached with 10% CP (group D) remained in the same range obtained for immediate bonding. Storage in artificial saliva also affected the control group, reducing its bond strengths to 53% of the original. ©2000 BC Decker Inc.
Keywords: bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; dentin bonding agent; drug derivative; hydrogen peroxide; peroxide; saliva substitute; single bond; urea; urea peroxide; analysis of variance; animal; cattle; chemistry; dental bonding; dental care; dentin; drug combination; materials testing; methodology; nonparametric test; randomization; tensile strength; time; Analysis of Variance; Animals; Bisphenol A-Glycidyl Methacrylate; Cattle; Dental Bonding; Dentin; Dentin-Bonding Agents; Drug Combinations; Hydrogen Peroxide; Materials Testing; Peroxides; Random Allocation; Saliva, Artificial; Statistics, Nonparametric; Tensile Strength; Time Factors; Tooth Bleaching; Urea